COVID-19 re-infection or persistent infection in patient with acute myeloid leukaemia M3: a mini review. (January 2021) - Tehrani, H.A.; Darnahal, M.; Nadji, S.A.; Haghighi, S.
Abstract: Coronavirus disease 2019 (COVID-19) pandemic has affected more than 40 million people worldwide. Some patients had episodes of symptom recurrence after the first episode of infection with variable intervals. There are multiple issues and hypotheses about re-infection or re-activation of the virus, especially in immunocompromised patients. In this paper, we present details of an individual with a recent history of COVID-19 who proceeded to acute myeloid leukaemia M3 and immunosuppression by chemotherapy, then we review some recently published articles about possible re-infection or re-activation.